Health Care Spending for Cardiovascular Disease under National Health Insurance Scheme in Indonesia Before and During COVID-19: Descriptive Analysis and PolicyRecommendations - Nurwahyuni, Atik; Soewondo, Prastuti; Nadjib, Mardiati; Farianti, Yuli; Mukhlisa, Mazda Novi; Wahyuningsih, Helmi; Mangunsong, Emmy Ridhawaty; Athiyah, Athiyah; Yunita, Yunita; Sayekti, Sekar Arum Handarbeni; Sari, Kurnia; Megraini, Amila (UI Scholars Hub, 2023)
The Cardiovascular disease (CVD) prevalence continues to increase. This study aims to identify the CVD spending and utilization in the Indonesia National Health Insurance (JKN) scheme 2017-2021 using the JKN claims classified by Disease Accounts analyzed descriptively. The CVD spending increased by 125,4 million in 2019 compared to 2017 and mostly for the hospital (91% in 2019) with the highest spending occurring in the age above 60 years. Moreover, the hospital inpatient spending was dominated during these five years. The highest portion of spending by severity level was at mild level, followed by moderate and severe levels. Health facilities’ capacities across the regions remain the issue in providing health services, especially for the CVD that require further treatment using advanced technology. The CVD cost continues to increase annually; fortunately, the JKN plays a key role as financial protection for participants. But, there was a decrease in the number of visits and spending on CVD during the COVID-19 pandemic because of lockdown policies and health systems shifting to provide capacity to overcome COVID-19. The decrease in the number of visits to health facilities raises the potential of being diagnosed later with more severe. As policy recommendations, strengthening primary care screening and hospital capacity across regions through implementing the Health System Transformation are expected to reduce the impact of these problems.